A new intravascular ultrasound‐guided stenting strategy compared with angiography on stent expansion and procedural outcomes in patients with positive lesion remodeling. Issue 2 (23rd January 2020) - Hakim, Diaa; Abdallah, Mouhamad; Effat, Mohamed; Al Solaiman, Firas; Alli, Oluseun; Leesar, Massoud A.
Abstract: Objectives: We investigated the role of a new intravascular ultrasound (IVUS)‐guided stenting strategy versus angiography on optimal stent expansion (OSE) and procedural outcomes in patients with positive lesion remodeling. Background: There are no IVUS criteria on how to achieve OSE. Methods: A total of 100 patients were assigned to a new IVUS‐guided stenting strategy (IVUS group) versus angiography‐guided stenting (Angio group). In the IVUS group, among patients with positive lesion remodeling, defined as a remodeling ratio (RR; lesion external elastic membrane (EEM) area/distal reference EEM area) >1.05, the stent was expanded with a balloon sized to the distal reference EEM diameter. In the Angio group, the stent was expanded by visual estimation. In both groups, IVUS was performed after postdilation. Results: Minimum stent area (MSA) and stent volume index were significantly larger in the IVUS versus Angio group (7.1 ± 1.9 vs. 5.9 ± 1.5 mm 2, and 8.7 ± 2.1 vs. 7.5 ± 1.8 mm 3 /mm, respectively; p < .01). The percentages of OSE, defined as an MSA ≥5.4 mm 2, MSA ≥90% of distal reference lumen area (DRLA), or MSA > DRLA, were significantly higher in the IVUS versus Angio group (80 vs. 56%, 78 vs. 54%, and 71 vs. 38%, respectively; p < .01). Stent underexpansion, malapposition, and residual reference segment stenosis were significantly higher in the Angio versus IVUS group (44 vs. 12%, 16 vs. 4%, and 12 vs. 0%, respectively; p < .05). In the IVUS group, owing to positive remodeling, there was no incidence of dissection or perforation. Conclusions: This new strategy of IVUS‐guided stenting in patients with positive lesion remodeling, compared with angiography, significantly increased stent expansion and decreased stent underexpansion, malapposition, and residual reference segment stenosis with no complications.